2020
DOI: 10.1002/pa.2307
|View full text |Cite
|
Sign up to set email alerts
|

Effects of renewable and non‐renewable energy consumption on CO2 emissions in India: Empirical evidence from disaggregated data analysis

Abstract: In this paper, we examined the relationship between renewable and non‐renewable energy consumption on CO2 emissions in India by taking disaggregated data from 1965 to 2018. In order to determine the effect of long‐run elasticity of independent variables on dependent variables, we have used ARDL bound testing approach. The directions of causality of the variables are investigated by Toda–Yamamoto Granger causality test. The long‐run results reveal that hydro energy consumption has a positive impact on CO2 emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(31 citation statements)
references
References 60 publications
3
28
0
Order By: Relevance
“…A recent study by Ansari et al (2020) (Beckerman, 1992;Zhengge, 2008;Jalil & Feridun, 2011;Khan et al, 2018;Ali et al, 2019;Lv & Xu 2019;Mahmood et al, 2020;Abdouli & Hammami, 2020). The studies found that the determinants like urbanization, renewable energy, and economic growth reduce environmental degradation (Martínez & Maruotti, 2011;Zhang et al 2015;Aye & Edoja, 2017;Sahoo and Sahoo, 2020a;Sahoo and Sahoo, 2020b). Ansari et al (2020c) examined the relationship between the energy-growth-environment relationship with top 10 carbon dioxide emitters countries.…”
Section: Renewable Energy Economic Growth and Environmental Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Ansari et al (2020) (Beckerman, 1992;Zhengge, 2008;Jalil & Feridun, 2011;Khan et al, 2018;Ali et al, 2019;Lv & Xu 2019;Mahmood et al, 2020;Abdouli & Hammami, 2020). The studies found that the determinants like urbanization, renewable energy, and economic growth reduce environmental degradation (Martínez & Maruotti, 2011;Zhang et al 2015;Aye & Edoja, 2017;Sahoo and Sahoo, 2020a;Sahoo and Sahoo, 2020b). Ansari et al (2020c) examined the relationship between the energy-growth-environment relationship with top 10 carbon dioxide emitters countries.…”
Section: Renewable Energy Economic Growth and Environmental Qualitymentioning
confidence: 99%
“…The study has covered the sample period from 1990 to for BRICS (Brazil, Russia, India, China, and South Africa) to explore the relationship between renewable energy, urbanization, human capital, and material footprint. All variables were transformed into logarithmic form to reduce the data sets fluctuation (Villanthenkodath & Arakkal, 2020;Sahoo and Sahoo, 2020a;Sahoo and Sahoo, 2019). This study Following (Ansari et al, 2020b;Nathaniel et al, 2020b) the specification of the model is as follows: ------------------------------------------Insert Table 1------------------------------------------…”
Section: Datamentioning
confidence: 99%
“…Few studies also discussed the determinants of environmental degradation with the macroeconomics variables like financial development, trade, economic growth are (Beckerman, 1992;Zhengge, 2008;Jalil & Feridun, 2011;Khan et al, 2018;Ali et al, 2019;Lv & Xu 2019;Mahmood et al, 2020;Abdouli & Hammami, 2020). The studies found that the determinants like urbanization, renewable energy, and economic growth reduce environmental degradation (Martínez & Maruotti, 2011;Zhang et al 2015;Aye & Edoja, 2017;Sahoo and Sahoo, 2020a;Sahoo and Sahoo, 2020b). Ansari et al (2020c) examined the relationship between the energy-growth-environment relationship with top 10 carbon dioxide emitters countries.…”
Section: Renewable Energy Economic Growth and Environmental Qualitymentioning
confidence: 99%
“…The study has covered the sample period from 1990 to for BRICS (Brazil, Russia, India, China, and South Africa) to explore the relationship between renewable energy, urbanization, human capital, and material footprint. All variables were transformed into logarithmic form to reduce the data sets fluctuation (Villanthenkodath & Arakkal, 2020;Sahoo and Sahoo, 2020a;Sahoo and Sahoo, 2019). This study Following (Ansari et al, 2020b;Nathaniel et al, 2020b) the specification of the model is as follows:…”
Section: Datamentioning
confidence: 99%
“…Extensive studies have explicitly stated that the consumption of non-renewable energy and the combustion of fossil fuels have devastating consequences for the environment, which, if not addressed, can cause irreparable damage to the environment and its few studies, the insignificant impact of the consumption of renewable energy on improving the quality of the environment has been concluded (Pata & Caglar (2021)). Furthermore, Sahoo & Sahoo (2020) found that the consumption of renewable hydropower energy amplified greenhouse emissions in India. Bölük & Mert (2014), in a study on sixteen European countries, deducted that the use of renewable energy has detrimental impacts on the environment and threatens the quality of the environment.…”
Section: Literature Reviewmentioning
confidence: 99%